The Role of Addition of Vitamin C in Iron Supplementation on Ferritin Serum Levels in Anemia Adolescent Females - Astuti, Nanik Dwi; Wirjatmadi, Bambang; Adriani, Merryana (Health Notions, 2018)
Prevention of iron deficiency anemia in Indonesia using ferrous sulfas blood-added tablets started since 1997. But iron deficiency anemia is still high, also in young women. Young women are vulnerable because of rapid growth and unhealthy their consumption patterns, which rarely consume fruits and vegetables that are a source of vitamin C. The purpose of this study was to analyze the addition of vitamin C in iron supplementation + folic acid to serum ferritin levels in adolescents females anemia. This research was an experimental quasi research. Design of research was Randomized Pre Post Test Control Group Design, with Double Blind treatment. This study had one treatment group and one control group, each group of 11 samples. The samples were chosen randomly with inclusion and exclusion. The collected data was processed using SPSS program with the analysis of paired t-test and independent t-test to test the difference of serum ferritin level. The results was showed the characteristics of respondents: age (p = 0.430), education of mother (p = 0.942) and nutritional knowledge of respondents (p = 0.928) in the same condition or both groups were had homogeneous characteristics. The pattern and level of food consumption were showed no different between control and traetment groups (p> 0.05). Serum ferritin levels showed difference between the two groups after treatment (p = 0.004). The study was showed vitamin C had role in increasing iron absorption and fill in storage of ferritin formation. Keywords: Anemia, Vitamin C, Iron supplement, Ferritin